2010
DOI: 10.1002/pen.21709
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a reverse molding sequence at the mesoscale for in‐mold assembly of revolute joints

Abstract: In-mold assembly and miniature molding are two technologies that have seen considerable advances in the past few years. These two technologies can be combined to realize miniature assemblies. Our previous work has shown that a significant change in the mold design is necessary to enable in-mold assembly at the mesoscale. Specifically, parts having the pins in the joint need to be molded before parts having holes. This sequence is reverse of the sequence typically used in macroscale assemblies. Moreover, specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Strength properties of the weld line area depend on the type of material being processed. It was shown that amorphous polymers are characterized by higher strength than semicrystalline ones . The viscosity of the polymer at the processing temperature plays a significant role.…”
Section: Introductionmentioning
confidence: 99%
“…Strength properties of the weld line area depend on the type of material being processed. It was shown that amorphous polymers are characterized by higher strength than semicrystalline ones . The viscosity of the polymer at the processing temperature plays a significant role.…”
Section: Introductionmentioning
confidence: 99%
“…The room temperature to which the polymers cool was assumed to be 28 C. We then calculated the interfacial frictional torque using Eqs. (1) and (2). These results are shown in Fig.…”
Section: Resultsmentioning
confidence: 52%
“…These methods, although highly inefficient, are popular processes for making macro scale mechanical assemblies. However, for fabricating miniature mechanical assemblies (joint dimensions < 1 mm) [1], manual assembly operations become very tedious and, in some cases infeasible. This is because, owing to the individual part sizes, it is difficult for a skilled human operator to assemble the parts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IMAs of various thermoplastic components to be assembled, for example, for joints , were investigated using adapted process techniques. These should make it possible to prevent the bending of the insert by the melt pressure . The insert injection molding with fiber inserts and high‐density polyethylene (HD PE) as encapsulation material to single polymer composites was investigated regarding to the interface properties in the literature [26].…”
Section: State Of Researchmentioning
confidence: 99%